Influence of Penumbral Reperfusion on Clinical Outcome Depends on Baseline Ischemic Core Volume. Issue 10 (October 2017) - Chen, Chushuang; Parsons, Mark W.; Clapham, Matthew; Oldmeadow, Christopher; Levi, Christopher R.; Lin, Longting; Cheng, Xin; Lou, Min; Kleinig, Timothy J.; Butcher, Kenneth S.; Dong, Qiang; Bivard, Andrew
Abstract : Background and Purpose—: In alteplase-treated patients with acute ischemic stroke, we investigated the relationship between penumbral reperfusion at 24 hours and clinical outcomes, with and without adjustment for baseline ischemic core volume. Methods—: Data were collected from consecutive acute ischemic stroke patients with baseline and follow-up perfusion imaging presenting to hospital within 4.5 hours of symptom onset at 7 hospitals. Logistic regression models were used for predicting the effect of the reperfused penumbral volume on the dichotomized modified Rankin Scale (mRS) at 90 days and improvement of National Institutes of Health Stroke Scale at 24 hours, both adjusted for baseline ischemic core volume. Results—: This study included 1507 patients. Reperfused penumbral volume had moderate ability to predict 90-day mRS 0 to 1 (area under the curve, 0.77; R 2, 0.28; P <0.0001). However, after adjusting for baseline ischemic core volume, the reperfused penumbral volume was a strong predictor of good functional outcome (area under the curve, 0.946; R 2, 0.55; P <0.0001). For every 1% increase in penumbral reperfusion, the odds of achieving mRS 0 to 1 at day 90 increased by 7.4%. Improvement in acute 24-hour National Institutes of Health Stroke Scale was also significantly related to the degree of reperfused penumbra ( R 2, 0.31; P<0.0001). This association was again stronger after adjustment for baseline ischemic core volume ( R 2, 0.41; P <0.0001). For each 1% of penumbra that was reperfused, the 24-hour National Institutes of Health Stroke Scale decreased by 0.069 compared with baseline. Conclusions—: In patients treated with alteplase, the extent of the penumbra that is reperfused is a powerful predictor of early and late clinical outcomes, particularly when baseline ischemic core is taken into account. Abstract : Supplemental Digital Content is available in the text.